EFEKTIVITAS PEMEKARAN WILAYAH DI INDONESIA: Antara Idealisme Otonomi Dan Realitas Ketergantungan Fiskal - Ervin Fahlevi; Ajeng Kusuma Andaning; Pandji Santosa (Post Graduate School of Government Science, 2025)
Regional proliferation in post reform Indonesia was intended to realize autonomous, self-sufficient local governments. However, many Newly Autonomous Regions (DOB) remain trapped in fiscal dependency, particularly on the central government’s General Allocation Fund (DAU). This study aims to analyze the effectiveness of regional proliferation by uncovering why DOBs consistently fail to achieve substantive autonomy across fiscal, institutional, and governance dimensions. Using a descriptive qualitative approach, the research was conducted in three purposively selected DOBs: Lebak (Java), Mahakam Ulu (Kalimantan), and Puncak Jaya (Papua). Data were collected through in-depth interviews with 15 key informants (including local officials, legislators, and community leaders), two weeks of participatory observation in each site, and document analysis (APBD, RPJMD, academic reports). Thematic analysis followed Braun and Clarke’s (2006) six-step model, supported by NVivo 14. Findings reveal chronic fiscal dependency, DAU contributes 70–77% of total revenue, while Local Own-Source Revenue (PAD) remains below 15%. Institutional capacity is weak, with limited technical expertise and outdated financial systems. Boundary conflicts persist due to inadequate spatial planning, and no systematic post-formation evaluation mechanism exists at the national level. These conditions confirm that autonomy remains formal rather than substantive. The study concludes that without mandatory post-split evaluations, incentives for PAD development, and targeted capacity-building, regional proliferation will continue producing administratively autonomous but functionally dependent entities.